Implementasi Program Kota Layak Anak Subklaster Perlindungan Khusus di Kelurahan Serua, Kota Tangerang Selatan - Nanda Agung Prasetyo Widodo; Moh. Amin Tohari (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The child-friendly city program is one of the programs where an area implements a child rights-based development system by trying to integrate several aspects such as government and community commitment and supported by human resources which in implementing it is carried out systematically, structured and sustainable, both in terms of policies that regulate this, to programs or activities. This research tries to see how the implementation of the child-friendly city program in providing special protection for children in Serua Village, South Tangerang. The research approach is qualitative with data collection techniques, namely interviews and documentary studies. This research uses George Edward's implementation theory which includes 4 aspects, namely resources, communication, bureaucratic structure, and disposition. The results showed that the implementation of the child-friendly city program in Serua Village has several success factors that have been carried out well, namely disposition and bureaucratic structure. Disposition is carried out with synergized cooperation between stakeholders, while the bureaucratic structure is well displayed in the form of coordination in the implementation of the child-friendly city. Meanwhile, other aspects that should be improved are communication and resources. Communication in this case is in the form of lack of public awareness and understanding of the program, while resources are related to budget limitations.